(untitled) (Sciences & Technologie. C, Biotechnologies, 2013)
In this work, we have study a chemical characterization of extracts of leaves of a medicinal plant which is the Peganum harmala L. Peganum harmala L. is belonging to the Zygophyllaceae family. This characterization is followed by the determination of the evaluation of the antimicrobial activity of three extracts (éthanolique, aqueous and hexane) on microbial pathogens to know their effects on these organisms. Phytochemical tests on the three extracts showed that the plant has a wealth of alkaloids. This high content of alkaloids gave him a very toxic. This study shows that the three extracts have antibacterial effects against Gram + and some Gram - except for E. coli and P. aeruginosa. Thus an inhibitory effect on yeasts and molds should be mentioned.